Glucagon-like peptide-1 receptor co-agonists for treating metabolic disease - Laurie L. Baggio; Daniel J. Drucker (Elsevier, 2021)
Background: Glucagon-like peptide-1 receptor (GLP-1R) agonists are approved to treat type 2 diabetes and obesity. They elicit robust improvements in glycemic control and weight loss, combined with cardioprotection in individuals at risk of or with pre-existing cardiovascular disease. These attributes make GLP-1 a preferred partner for next-generation therapies exhibiting improved efficacy yet retaining safety to treat diabetes, obesity, non-alcoholic steatohepatitis, and related cardiometabolic disorders. The available clinical data demonstrate that the best GLP-1R agonists are not yet competitive with bariatric surgery, emphasizing the need to further improve the efficacy of current medical therapy. Scope of review: In this article, we discuss data highlighting the physiological and pharmacological attributes of potential peptide and non-peptide partners, exemplified by amylin, glucose-dependent insulinotropic polypeptide (GIP), and steroid hormones. We review the progress, limitations, and future considerations for translating findings from preclinical experiments to competitive efficacy and safety in humans with type 2 diabetes and obesity. Major conclusions: Multiple co-agonist combinations exhibit promising clinical efficacy, notably tirzepatide and investigational amylin combinations. Simultaneously, increasing doses of GLP-1R agonists such as semaglutide produces substantial weight loss, raising the bar for the development of new unimolecular co-agonists. Collectively, the available data suggest that new co-agonists with robust efficacy should prove superior to GLP-1R agonists alone to treat metabolic disorders.